Delivering convenient service and better zakat distribution management through UiTM Pulau Pinang eZakat system / Naemah Abdul Wahab ... [et al.] - Abdul Wahab, Naemah (2015)
Zakat Unit UiTM Pulau Pinang was established in October 2010 to serve as the development, collection and distribution of zakat fund to entitled students (asnaf). This unit will assist the underprivileged students whom categorized as asnaf in the form of tuition fees, living wages, health relief and Aidilfitri assistance. The previous procedures of zakat application are inefficient since the students had to fill up manual forms and going through bureaucracies before being called up for the interview session. The applicants are unenthusiastic to apply for zakat aid because of the incompetent system. Other than that, the prior procedures that are mostly done manually had complicate the Zakat Unit staffs to keep potential asnaf's information, displaying applicant's list for decision making processes, interview calling procedures as well as generating reports for documentation purposes. Therefore, this paper discusses on the application of an online zakat system called eZakat to overcome these major weaknesses. Initial results shows that the use of eZakat has improve efficiency of zakat applications in Zakat Unit. It has also significantly assisted the zakat applicants, Zakat Unit, HEP as well as Treasury Unit staffs of UiTM Pulau Pinang for a better delivery service and a more competent distribution zakat management.